(untitled) (Al-NASR, 2024)
Michael Oakeshott’s epistemology revolves around the concept of Modes of the understanding of the meanings of the world. These meanings had been mediated by our forefathers and had been descended to us through generation to generations. The whole of these meanings is the common capital for all human beings irrespective of terrestrial affiliation or adherence to any theology or association to any race. Without learning the meanings, we are just a bipod specie or Homo Erectus and Homo Sapiens but not ‘Beings Human’. Thus he founded his epistemology on concept of ‘learning to be human’ and he made a difference between a ‘human being’ and ‘being human’. Islamic teachings also support Oakeshott’s ideas regarding, Epistemology, Theory of Knowledge and educational Philosophy.